Alternativas Para El Monitoreo De Asentamientos Diferenciales De Edificaciones (2024)
Structural settlements are movements caused by a subsidence or some type of consolidation of the underlying soil. These deformations can alter the stability and functionality of buildings and any other type of structure. These settlements usually occur regularly due to very common causes such as inadequate soil compaction during formation, the presence of expansive or unstable soils and the variation in groundwater levels. Factors such as soil overload and excessive extraction of groundwater and changes in applied loads over long periods of time can also be a cause of these.